Re-theorizing the welfare state and the political economy of neoliberalism's war against it - Thomas I. Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
This paper argues neoliberalism is engaged in a war against the welfare state. At issue are competing views regarding the size of the welfare state and how it should be organized. In waging this war, neoliberalism seeks to politically discredit the traditional welfare state and change the economic structure so that the latter becomes unviable. The paper presents a new theoretical framework that distinguishes between modes of production and financing of the welfare estate. Neoliberalism's war rests on ideologically grounded criticisms drawn from mainstream economics; implementation of policies that undermine social solidarity toward the welfare state; exploiting pressures fostered by neoliberal globalization; and misrepresentations about affordability. The welfare state was critical in saving capitalism from itself after World War II. It is a way of embedding the market system so as to produce socially acceptable outcomes that are politically stable. Neoliberalism's war promises a body blow against shared prosperity. More ominously, it may so dis-embed the market system as to recreate conditions Polyani (1944) blamed for the rise of fascism in the 1930s.
Keywords: H1; H10; H50; 330; Welfare state; neoliberalism; mode of production; mode of financing